Residents’ Expectation and Perception of Sustainable Housing Development - Abdul Rahman, Anis Suhaila; Jailani, Junaidah (Recent Trends in Civil Engineering and Built Environment, 2021)
This paper presents a study on population perception and readiness to implement a sustainable housing system in Malaysia. Understanding sustainable housing can motivate developers to make judgments, as there is a lot of demand. In addition, government attention can be drawn to the fact that sustainable development in Malaysia is more focused on government buildings. Once the government has given this, it will contribute to the incentive of the builder. However, before implementing sustainable housing as a whole, it is also necessary to understand the barriers to achieving the objectives and resolving issues.